Lay Ecclesial Ministry: Pathways Toward the Future - Seton Hall University (Rowman & Littlefield Publishers, 2010)
The role of lay ecclesial ministers—professionally prepared laity who serve in leadership roles—is becoming critically more important in the life of the Catholic church. In Lay Ecclesial Ministry, theologians and pastoral leaders from diverse disciplines provide a deeper understanding, envision future direction, and offer inspiration for these new ministers and the community of the church. Building on the themes of the first official document addressing lay ecclesial ministry, Co-workers in the Vineyard of the Lord, approved by the U.S. Conference of Catholic Bishops in 2005, this book delves deeply into key topics. Authors reflect on dimensions of the Catholic tradition to enrich our understanding of this new reality of lay ministry in the church, to envision future developments, and to offer inspiration. Contributors draw on a variety of theological perspectives, including canon law, church history, ecclesiology, liturgy, and scripture, to ground understanding of lay ecclesial ministry within the Catholic tradition and to chart direction for further response to this newly emergent ministry. The book also offers inspiration and models of service to lay ministers, looking to stories of the saints and communities of vowed religious. Lay Ecclesial Ministry is an essential resource for the Catholic community in understanding and building upon this new and increasingly important component of church life.